Coelomocyte activity and pathogenicity description of nypa palm worm (Namalycastis rhodochorde) after injection with Aeromonas sp. NrBF9 isolated from fecal pellets of nypa palm worm (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Yanti AH, Kurniatuhadi R, Setyawati TR, Ramadani R. 2022. Coelomocyte activity and pathogenicity description of nypa palm worm (Namalycastis rhodochorde) after injection with Aeromonas sp. NrBF9 isolated from fecal pellets of nypa palm worm. Biodiversitas 23: 5439-5445. Coelomocytes in the Annelida group play a role in the immune system by recognizing and destroying foreign objects that enter the body. A study of the character and type of nypa palm worm coelomocytes (Polychaetes) can provide an overview of nypa palm worm resistance to pathogenic microorganisms. Thus researchers can determine the resistance of worms during cultivation based on developmental stages. This study aimed to determine the total and differential coelomocytes of nypa palm worms induced by Aeromonas sp. NrBF9, and to describe the pathogenicity of Aeromonas sp. NrBF9 against palm worms. Observation of the total number of coelomocytes, differential coelomocytes, and character of coelomocytes was carried out after injecting pathogenic bacteria directly into the body of the nypa palm worm. The bacterial test suspension was divided into three treatments, namely P1 (2.7×107 cells/mL of Aeromonas sp. NrBF9), P2 (3.2×105 cells/mL of Aeromonas sp. NrBF9), and P3 (3.4 × 103 cells/mL of Aeromonas sp. NrBF9). Non-induced worms were used as controls. The treated worms were then incubated for 72 hours. The total number of coelomocytes was calculated using the cubicle count method, whereas differential coelomocytes using the smear method. The pathogenicity of the nypa palm worms was described descriptively by determining the morphology of the nypa palm worms after 72 hours of bacterial injection. The results showed an increase in the total number of coelomocytes of nypa palm worms in all injection treatments with Aeromonas sp. NrBF9. The highest total coelomocyte count was obtained in treatment P1(10-3) of 70.58 x 103 cells/mm3. The number of differential coelomocytes also increased, especially in type II and IV-amoebocyte cells. The description of disease resistance and symptoms of nypa palm worms after being induced by Aeromonas sp. NrBF9 in the form of sores and discoloration of the internodes near the injection site became white and healed on the third day. The description of the type and character of coelomocytes and the resistance of nypa palm worms to pathogens are expected to be the basis for understanding worm cultivation activities in the future.
Keywords: Aeromonas sp. NrBF9, coelomocytes, immune response, nypa palm worms